Dense Hydrogen-Bonded Assembly of Hydrogen-Rich Cations and Pentazolate Anions: A Series of Highly Insensitive Ionic Salts - Lianghe Sun; Hongwei Zhu; Shuaijie Jiang; Xiaofeng Yuan; Guoping Lu; Ming Lu; Yuangang Xu (Molecules)
Compounds containing the pentazolate anion (cyclo-N5−) represent a distinctive group of energetic materials that have received extensive attention in recent years. Cyclo-N5− was used as a polynitrogen anion for the syntheses of energetic salts through metathesis reactions. Propamidinium (1), 5-amino-4-carbamoyl-1H-imidazol-3-ium (2), (1H-1,2,3-triazol-4-yl)methanaminium (3), 5-amino-4H-1,2,4-triazol-1-ium (4), 5-amino-3-methyl-4H-1,2,4-triazol-1-ium (5), and amino(pyrimidin-2-yl)methaniminium (6) pentazolates were obtained with high yields (>80%), and their crystal structures were confirmed through single-crystal X-ray diffraction analyses. Hirshfeld surface analyses and 2D fingerprint plots generated by CrystalExplorer17 demonstrated that these compounds exhibited extensive hydrogen-bonding networks in their crystal packing. Mechanical sensitivity tests showed that all the prepared salts were highly insensitive (IS > 35 J, FS > 360 N), providing valuable insights for the further exploration of broader energetic materials containing cyclo-N5−.